Human development report 2016 : human development for everyone (United Nations Publications, 2016)
This publication explores how work can enhance human development, given that the world's workforce is changing rapidly, and even with progress, significant human development challenges still remain. It takes a broad view of going beyond jobs and examines the linkage between work and human development.